Synthesis of 11C-Labelled Symmetrical Ureas via the Rapid Incorporation of [11C]CO2 into Aliphatic and Aromatic Amines - Dheere, Abdul Karim Haji; Bongarzone, Salvatore; Taddei, Carlotta; Yan, Ran; Gee, Antony D. (Synlett, 2015)
An efficient method to radiolabel symmetrical [11C]ureas using 1,8-diazabicycloundec-7-ene (DBU) and cyclotron-produced [11C]CO2 has been developed. [11C]urea derivatives were obtained when aliphatic and aromatic amines were used with excellent radiochemical yields (RCYs) of over 70%. The mechanism of the reaction is proposed on the basis of control experiments. This simple and robust methodology provides a powerful tool to prepare 11C-labelled ureas previously inaccessible by existing methods and enable their utilisation for in vivo molecular imaging applications.
Keywords: carbon-11; carbon dioxide; Mitsunobu reaction; symmetrical urea; DBU